Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3846/tede.2021.15699
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Performance Evaluation Framework for New Service Development in the Healthcare Industry Using Hybrid Ism and Anp

Abstract: Today, the innovative activities of companies in new service development (NSD) have an undeniable contribution to the economic development of countries. Given the recent advances in the healthcare industry, the issue of NSD and performance management of firms operating in this industry has received special attention of researchers and decision makers. A review of previous research shows that on the one hand there is no agreement among experts on NSD performance measurement criteria and on the other hand there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Charan et al [45] identified fourteen factors with inputs from seven experts for their work in supply chain management. Similarly, Dahooie et al [46] identified seventeen factors with the combined input from the researched data and expert's opinion in the healthcare industry. Singh and Rathi [47] stated sixteen factors through a questionnaire survey of industrial experts and academicians on six sigma barriers in small-and medium-sized industries.…”
Section: Methodsmentioning
confidence: 99%
“…Charan et al [45] identified fourteen factors with inputs from seven experts for their work in supply chain management. Similarly, Dahooie et al [46] identified seventeen factors with the combined input from the researched data and expert's opinion in the healthcare industry. Singh and Rathi [47] stated sixteen factors through a questionnaire survey of industrial experts and academicians on six sigma barriers in small-and medium-sized industries.…”
Section: Methodsmentioning
confidence: 99%
“…The most important criterion to consider in sustainable project selection is project cost, followed by novelty and uncertainty as the second and third most important criteria, respectively. Dahooie et al, 2021 [56] Allow for interaction between different decision makers, considering multiple and sometimes conflicting criteria.…”
Section: Ocampo and Clark 2017 [55]mentioning
confidence: 99%
“…Table 1 shows some example of using these techniques with their application in performance measurement. Many researchers have tried to use MCDM techniques, such as analytic hierarchy process (AHP) (de Felice et al, 2015; Ikram et al, 2020; Yaghoobi & Haddadi, 2016), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) (Bai et al, 2014; Gök‐Kısa et al, 2021), analytic network process (ANP) (Dahooie et al, 2021; Digalwar et al, 2020; Van Horenbeek & Pintelon, 2014), Preference Ranking Organisation Method for Enrichment Evaluations (PROMETHEE) (Ishizaka & Resce, 2021; Schwartz & Göthner, 2009) and Decision‐Making Trial and Evaluation Laboratory (DEMATEL) (Kilic & Yalcin, 2021; Tseng et al, 2018) or a mixture of these techniques (Guru & Mahalik, 2019; Yurdakul* & Ic, 2005).…”
Section: Introductionmentioning
confidence: 99%